Sustainable Business Model Design: A Case Study of Aromatherapy Balm Stick Product “Seraphie” - Sangadah, Hanik Atus; Indrianingsih, Rohayati Suci (Universitas Muhammadiyah Pontianak, 2026)
Seraphie is an innovative aromatherapy balm stick developed as an alternative topical product. This study aims to: (1) assess the product's feasibility through market testing, (2) design a sustainable business model using the Triple Layered Business Model Canvas (TLBMC), and (3) analyze decision-making using the Plus Minus Implication Analysis (PMIA) method. Results show that the fourth prototype (Peaceful Dream variant) achieved an MVP score of 3.99 (“liked” category). The sustainable business model integrates economic, social, and environmental layers, with PMIA scores indicating that the current business structure is feasible and suitable for further development.